Development of an Entrepreneurship E-Book with a Realistic Approach to Improve Student Fashionpreneurship Competence - Retnasari, Dian; Nurlita, Asri Andarini (Universitas Negeri Semarang, 2024)
Fashionpreneurship is one of the competencies that fashion education study program students must possess. Therefore, it is essential to have an e-book with a realistic approach as a companion media that can help improve student competence. The study aimed to produce an e-book and determine the feasibility of e-books with a realistic approach. This type of research is development research (Research & Development). This research uses the 4D development model: define, design, develop, and disseminate. The data collection method used observation, document study, interview, and questionnaire. Data about the feasibility of e-books were analyzed using quantitative descriptive statistics. The results of this study indicate the feasibility of teaching materials based on the assessment of material experts, media experts, small-scale trials, and large-scale trials, which obtained very feasible category results. Thus, the developed entrepreneurship e-book can be used by students to improve their fashionpreneurship competencies.